GRP-002 A Case Report: Management of Pain After Subcutaneous Injection of Treprostinil. (12th March 2013) - Collomb, M; Chevallard, H; Chapuis, C; Foroni, L; Calop, J; Allenet, B; Bedouch, P
Abstract : Background: Treprostinil is a prostacyclin analogue indicated for the treatment of Pulmonary Arterial Hypertension (PAH) for patients with functional NYHA class III. The administration is a continuous subcutaneous infusion. It is recommended that the treatment is initiated incrementally to reach a target dose, in intensive care. Injection site pain and local reactions (respectively 85% and 83% of patients) cause treatment cessation in 8% of cases [1]. Purpose: To describe the role of multidisciplinary care in the management of pain due to treprostinil treatment. Materials and Methods: A descriptive study of a patient with pain due to subcutaneous injection of treprostinil. We collected information from the clinical and pharmacotherapeutic histories. A systematic literature search was performed about practical considerations for subcutaneous treprostinil in PAH. At Grenoble Hospital, the pain of treprostinil is managed by patient education [2] conducted by pharmacists, doctors and nurses belonging to different units. Results: Treprostinil treatment was initiated on 19 May 2011, on a 43 year-old patient with idiopathic pre-capillary NYHA III PAH (bosentan and tadalafil not effective; right-heart catheterization 80/30/50 mmHg PAP). The 6-minute-walk test was 544 metres. The initial dose is 1 ng/kg/min for a target dose of 40 ng/kg/min. The initial tolerance was good (Visual Analogue scale (VAS): 3; controlled by paracetamol). Doses were increased with an increment of 1 ng/kg/day. On May 30, 2011, with 10 ng/kg/min dose, the pain was intense (VAS: 8) despite analgesic treatment (paracetamol + tramadol), application of hot/cold packs and diclofenac gel. Mathier's work suggested changing the injection site (abdomen) and limiting the rotation. On July 08, 2011, the pain was controlled (VAS: 2) decreasing 4 days after changing the injection site [1]. The dose was 38 ng/kg/min, the NYHA stage was going down to II, while echocardiography showed persistent right dysfunction. By September 13 the desired dose had been reached (40 ng/kg/min), the pain had disappeared (VAS: 0), the patient was not taking analgesics and the injection site was being changed every 3 weeks. The effectiveness of the treprostinil treatment was demonstrable clinically and echographically. Conclusions: Intense pain due to treprostinil may require discontinuation of effective treatment. This case shows that multidisciplinary care with the use of simple measures allows this common side effect to be managed and cessation of treatment prevented. References: Subcutaneous treprostinil in pulmonary arterial hypertension: Practical considerations – MA Mathier – J Heart Lung Transplant . 2010 Nov;29(11):1210–7. Epub 2010 Sep 19. Bedouch et al, Pharmacists involved in patient education: a pharmacist collaborative care programme for pulmonary arterial hypertension. Int J Clin Pharm ( in press ). No conflict of interest.